2022
DOI: 10.1021/acs.jpclett.1c03909
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Engineering of Conjugated Polymers for High-Performance Organic Field-Effect Transistors

Abstract: Past decades have witnessed the rapid development of conjugated polymers because of their promising semiconducting properties and applications in organic field-effect transistors (OFETs). Recent studies have shown that side-chain engineering of conjugated polymers is an efficient strategy to increase semiconducting performance. This Perspective focuses on the side-chain modulation of conjugated polymers and evaluating their effects on the performance of OFETs. The challenges and potential applications of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 119 publications
0
31
0
Order By: Relevance
“…On the other hand, the chemical structures also have a critical impact on μ of SPs. Subtle changes in a chemical structure could induce remarkable differences in μ for similar SPs, including different types of solubilizing alkyl chains, anchoring the position of substituted groups, , isomerization of polymerized monomers, , structural regularity of polymer backbones, and so forth. Among these, the structural regularity effects have been extensively studied. As early as 1999, Sirringhaus et al found that the head-to-tail regioregular P3HT (HT- rr -P3HT) had a μ h of 0.1 cm 2 V –1 s –1 , while the low-regioregularity P3HT only exhibited a very low μ h of 2 × 10 –4 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, the chemical structures also have a critical impact on μ of SPs. Subtle changes in a chemical structure could induce remarkable differences in μ for similar SPs, including different types of solubilizing alkyl chains, anchoring the position of substituted groups, , isomerization of polymerized monomers, , structural regularity of polymer backbones, and so forth. Among these, the structural regularity effects have been extensively studied. As early as 1999, Sirringhaus et al found that the head-to-tail regioregular P3HT (HT- rr -P3HT) had a μ h of 0.1 cm 2 V –1 s –1 , while the low-regioregularity P3HT only exhibited a very low μ h of 2 × 10 –4 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 84%
“…The introduction of electron‐withdrawing groups (EWGs), such as fluorine (F), [ 9‐16 ] cyano (CN), [ 17‐20 ] imide, [ 12,21‐24 ] amide, [ 21,25‐26 ] and carbonyl (C=O) [ 27 ] groups in building blocks is a common strategy to lower the HOMO and LUMO levels of CPs. Many building blocks containing F atom(s) have been reported for the synthesis of high‐performance n‐type or ambipolar conjugated polymers.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Brominated T-TzII and Se-TzII were synthesized according to our published procedure, 29,30 using the alkyl sidechain with the branch point three atoms away from the conjugated backbone, since it has been proved that this sidechain engineering protocol is efficient to improve the crystallinity of the resulting polymers. [45][46][47] Stannylated T-DPPs with two different sidechains (C12 and C20, as illustrated in Scheme 1, with the branch point only one-atom-away from the core structure) were purchased directly from commercial resources. Our initial goal of choosing the two different sidechains is to testify which one could guarantee the solubility of the resulting polymers.…”
Section: Polymer Synthesis and Characterizationmentioning
confidence: 99%